Structuralism: Hemingway’s novel - memoir “A moveable feast” in the light of structuralist and myth criticism - Sarinyan, Mane
The article explores methodological issues in literary criticism that have their origins in structural linguistics, a theoretical framework established by Ferdinand de Saussure in the early twentieth century. It examines the utilization of the principles of structuralism in literary criticism for the study of literature and literary works. The subject matter of the article is the application of structuralist and myth-critical methodologies in analy ing Hemingway’s novel “A Moveable Feast”. The aim of the article is to examine the underlying structures and archetypes in the novel, shedding light on its symbolic and universal aspects. The analysis explores elements such as the title, structure, genre, and archetypal patterns within the narrative, revealing the novel’s consistency with the rite-of-passage model and quest myth framework. The novelty of the article consists in investigating Hemingway’s novel from structuralist and myth-critical perspectives. Հոդվածում անդրադարձ է կատարվում ստրուկտուրալիզմի և ծիսամիֆոլոգիական քննադատության հարցերին, որոնք որպես մեթոդաբանական հիմք էին ընդունում քսաներորդ դարասկզբին Ֆերդինանդ դը Սոսյուրի կողմից մշակված կառուցվածքային լեզվաբանության սկզբունքներն ու դրույթները: Ստրուկտուրալիզմը էապես փոխեց գրականագիտության գիտականացման հիմունքը: Գրական երկից անջատելով սոցիալ-պատմական, փիլիսոփայական շերտերը` նոր քննադատները գեղարվեստական երկի ուսումնասիրության մեթոդաբանական հիմք ընդունեցին կառուցվածքային մեթոդը՝ հատկապես առանձնացնելով պոետիկայի հարցերը և առաջնությունը տալով գեղարվեստական երկում որոշակի մոդելների, սիմվոլների և արքետիպերի գործառնությանը: Հոդվածում Հեմինգուեյի «Տոն, որ միշտ քեզ հետ է» վեպը դիտարկված է արքետիպային ձևույթում՝ որոնման միֆի շրջանակներում: Վերլուծությունը քննում է կառուցվածքային տարրերը՝ վերնագիրը, ժանրային առանձնահատկությունը, արքետիպային մոդելները: Հոդվածի նորույթը Հեմինգուեյի վեպի ստրուկտուրալիստական և միֆաքննադատական քննությունն է: В данной статье рассматриваются методологические проблемы литературной критики, которые уходят корнями в структурную лингвистику - теоретическую основу, созданную Фердинандом де Соссюром в начале XX века. Она рассматривает, как принципы структурализма, заимствованные из лингвистики, были применены к изучению литературы. Предметом статьи является использование структуралистских и мифологических методологий при анализе произведения Хемингуэя “Праздник, который всегда с тобой”. Целью данной статьи является изучение основных структур и архетипов в романе, раскрывая его символические и универсальные аспекты. Анализ исследует такие элементы, как заглавие, структура, жанр и архетипические модели в повествовании, выявляя соответствие романа архетипу мифа-квеста. Новизна статьи заключается в исследовании романа Хемингуэя с позиций структурализма и мифокритики.
Keywords: Literature